A Preliminary System-Level Exploratory Study of Behavior-Based Modifications to Cage-Free Housing in KUB Chickens - Utami, Kartika Budi; Dewi Kristanti, Novita; Aini, Fitria Nur; Susanti, Eka Febri; Pramuja, Arya; Wardana, Mochamad Riski (Jurnal Ilmu-Ilmu Peternakan, 2026)
Standard cage-free systems may not fully accommodate the active behavior of local chickens, potentially affecting welfare and productivity. This preliminary study evaluated behavior-based modifications to cage-free housing and their associations with physiological responses, behavioral expression, and egg quality in Kampung Unggul Balitnak (KUB) pullets. Sixty 20-week-old pullets were assigned to a control group (Humane Farm Animal Care [HFAC] standards) or a modified group with reduced stocking density (6–7 hens/m²), a 1:3 nest-to-hen ratio, and multi-level perches. Welfare indicators included plasma corticosterone levels (measured by enzyme-linked immunosorbent assay, ELISA) and behavioral observations. At the same time, egg quality was assessed based on physicochemical properties and microbiological safety in accordance with the Indonesian National Standard (SNI). Corticosterone levels were comparable between the modified (1.69±0.56 ng/mL) and control (1.48±0.49 ng/mL) groups. The modified housing system was associated with more frequent expression of natural behaviors, such as dust bathing and perching, and a lower frequency of aggressive interactions compared with the control system. Egg quality parameters were similar between groups, and microbiological contamination remained below SNI safety thresholds. The modified group showed a numerically higher yolk cholesterol levels (764.94 mg/100 g) than the control group (634.24 mg/100 g). In conclusion, this preliminary study suggests that behavior-based modifications to cage-free housing may enhance behavioral expression in KUB chickens without compromising egg safety. However, the findings are limited by the preliminary design and lack of experimental replication. Future replicated studies are needed to validate these observations.